The Liquidation of Art in Contemporary Art - Bergande, Wolfram (The Nordic Journal of Aesthetics, 2016)
In this paper, the concept of liquidation (Verflüssigung) from the chapter on Self-consciousness in Hegel’s Phenomenology of Spirit is reconstructed and then used to deconstruct the systematic transition from sculpture to painting in the passage on the “System of the individual arts” in G.W.F. Hegel’s Aesthetics: Lectures on Fine Art. The aim is to show that such a deconstructed version of Hegel’s art philosophy provides a valid conceptual framework for the analysis of modern, particularly postmodern and contemporary art, which results as liquid or liquidated art. Damien Hirst’s For the Love of God is discussed as major evidence for the concomitant neo-Hegelian claim that modern art has discursive reflection as its necessary supplement.